Work Family Conflict and Career Satisfaction in Banking Sector of Nepal - Regmi Adhikary, Jyoti (NRB Economic Review, 2018)
While a wealth of research has examined how work family conflict (WFC) affects negative work outcomes, there is limited research investigating the relationship of WFC with positive work outcomes. Using a sample of 381 Nepali banking professionals, this study examined the relationships of WFC with career satisfaction and social support. Study also explored how the socio demographic variables affected WFC, career satisfaction, and social support. Analyses indicated no statistically significant relationships of WFC with career satisfaction. Results also indicated association of social support from both work and family with increased career satisfaction. However, social support did not emerge as a significant moderator in the relationship between WFC and career satisfaction. In case of socio-demographic variables, only organizational grouping stood out as significant difference in the level of WFC experience among banking employees. This study has various theoretical and practical implications that are presented along with further research issues.